Report.“Exploration of wild banana populations in Papua New Guinea”, 7-17 June 2017 - Sardos, J.; Paofa, J.; Janssens, S.; Vanden Abeele, Samuel; Roux, N.; Panis, Bartholomeus (2017)
This report documents the exploration of wild banana populations on the East coast of Papua New Guinea in June, 2017, with the aim of collecting wild specimens for population genetics studies. The collecting team visited two provinces on the East coast: in Madang province, they collected samples of M. acuminata banksii M. schizocarpa and M. peekelii ssp. angustigemmawhile M. acuminata ssp. banksii, M. schizocarpa, M. maclayi spp. maclayi var maclayi and M. balbisiana were collected in Morobe Province. In addition to leaf samples, seeds were also collected that will be studied and conserved as part of the ITC Musa seedbank being established by Bioversity International and the Botanical Garden of Meise